(untitled) (Jurnal Bahasa, 2004)
This article is an approach to negative expressions and their issues in Malay and Japanese. Using translated novels, negative expressions in both languages were collected and analyzed. Quantitative analysis resulted that more than 60 percent of Malay negatives expressions were also expressed in negative in Japanese. However, when compared to Malay, Japanese shows tendencies to use negative phrases rather than affirmative. For instances, negative phrases were used when indicating imperative and obligation in Japanese sentences. These sentences contained negatives constituent, but semantically they are affirmative.